Heart deformation analysis: The distribution of regional myocardial motion patterns at left ventricle - Lin, Kai (Int J Cardiovasc Imaging, 2016)
The aim of the present study was to test the hypothesis that heart deformation analysis (HDA) is able to discriminate regional myocardial motion patterns on the left ventricle (LV). Totally 21 healthy volunteers (15 men and 6 women) without documented cardiovascular diseases were recruited. Cine MRI was performed on those subjects at four-chamber, two-chamber, and short-axis views. The variations of segmental myocardial motion indices of the LV, which are measured with the HDA tool, were investigated. Regional displacement, velocity, strain and strain rate were compared between lateral wall and septal wall using t-tests. There are significant variations (CoV = 18.0% to 72.4%) of myocardial motion indices (average over 21 subjects) among 16 myocardial segments. There are significant differences (p < 0.05) between displacement, velocity, strain and strain rate measured at lateral and septal areas of the LV. In conclusion, HDA is able to present different regional LV motion patterns from multiple aspects in healthy volunteers.